Ocena zmiany warunków hydrologicznych na terenach zurbanizowanych z wykorzystaniem technik GIS = GIS-based assessment of changes related to hydrological conditions in urban areas - Danuta Szumińska; Tomasz Giętkowski; Sebastian Czapiewski (Kazimierz Wielki University, 2015)
Szumińska Danuta, Giętkowski Tomasz, Czapiewski Sebastian. Ocena zmiany warunków hydrologicznych na terenach zurbanizowanych z wykorzystaniem technik GIS = GIS-based assessment of changes related to hydrological conditions in urban areas. Journal of Education, Health and Sport. 2015;5(5):173-182. ISSN 2391-8306. DOI 10.5281/zenodo.17494 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A173-182 https://pbn.nauka.gov.pl/works/559397 http://dx.doi.org/10.5281/zenodo.17494 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015.   Ocena zmiany warunków hydrologicznych na terenach zurbanizowanych z wykorzystaniem technik GIS   GIS-based assessment of changes related to hydrological conditions in urban areas   Danuta Szumińska1, Tomasz Giętkowski, Sebastian Czapiewski   Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy email: dszum@ukw.edu.pl1   Streszczenie   W artykule zaprezentowano możliwości wykorzystania technik GIS do przeprowadzenia analizy zmiany warunków hydrologicznych. Badania przeprowadzono na terenie zurbanizowanym, na którym dokonano zmian rzeźby oraz sposobu użytkowania terenu. Spowodowało to pojawieniem się problemów z odwodnieniem terenu, przede wszystkim w czasie wzmożonego zasilania z opadów deszczu i roztopów śniegu. W celu określenia przyczyn występujących problemów porównano rzeźbę terenu oraz wyznaczono kierunki odpływu wód powierzchniowych przed i po zagospodarowaniu działki d (Ryc. 1). Czasochłonne i kosztochłonne badania geologiczne wykonano w minimalnym zakresie (Tab. 1) i zostały one wykorzystane jako informacja uzupełniająca, pozwalająca na ocenę możliwości infiltracji wody w podłoże. Na podstawie przeprowadzonych badań stwierdzono, że główne przyczyny problemów z odwodnieniem terenu związane są ze stworzeniem barier w postaci podmurówek ogrodzeń zlokalizowanych prostopadle do kierunków odpływu wody (Fot. 1, Fot. 2). Zmiany rzeźby były w analizowanym przypadku czynnikiem mniej istotnym.   Słowa kluczowe: warunki hydrologiczne, infiltracja, model rzeźby terenu, kierunki odpływu, użytkowanie terenu, tereny zurbanizowane.   Abstract   The paper discusses the possibilities of employing GIS for conducting analysis of changes in hydrological conditions. The study was carried out in an urban area featuring altered relief and use of land. This caused problems with draining the terrain, particularly at times of increased rainwater and meltwater supply. In order to identify the causes of the occurring problems, we compared land relief prior and after the plot was developed, as well as indicated the directions of surface water runoff (Fig. 1). Time-consuming and expensive geological research activities were restricted to minimum (Tab. 2) and the data thus obtained were used as supplementary information to assess the capacity for water infiltration into the ground. The study enabled us to draw a conclusion that the main cause of the drainage problems is related to the construction of barriers, i.e. fencing base running perpendicular to the direction of water runoff  (Photo 1 and 2). The changes in land relief were in this case of lesser importance.   Key words: hydrological conditions, infiltration, digital elevation model, runoff directions, land use, urban areas.